THE EFFECT OF FINANCIAL DISTRESS ON PROFITABILITY (STUDY CASE IN NON-FINANCIAL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2014 – 2018) - admin, Yunita B1024161001 (Jurnal Manajemen Update, 2021)
ABSTRACTOne of the company’s objectives is to make a profit. Profit is one of the factors that influence a company’s ability to survive. In one of the efforts to achieve these goals, the company will always try to establish various strategies that are right for profit. However, the company at any time has the potential to face financial distress, and it may have an impact on many things if it does not take the right decisions to overcome this problem so that it may interfere with the company’s performance in obtaining profits. Therefore, this study focuses on analyzing the effect of financial distress on the profitability of companies listed on the Indonesia Stock Exchange.  This study used secondary data from annual reports of the studied companies of the sample of 50 companies listed on the Indonesia Stock Exchange with a duration of 5 years, resulting in 250 observations. The dependent variable of profitability is determined by the return on assets (ROA), return on equity (ROE), net profit margin (NPM), and gross profit margin (GPM). Meanwhile, the independent variable of financial distress is determined by Altman Z-score modified. The research analysis uses the random effect model and fixed-effect model in the panel data regression process. The final results of this study indicate that financial distress has a positive and significant effect on ROA, ROE, and NPM by using the random effect model. Financial distress also has a positive and significant effect on GPM by using the fixed effect model. REFERENCESAgusti, C. (2013). Analisis factor yang mempengaruhi kemungkinan terjadinya financial distress. Semarang: Skripsi Sarjana Jurusan Akuntansi pada Fakultas Ekonomi dan Bisnis Universitas Diponegoro.Aktas, N., Eric, d. B., & Frederic Lobez, J.-C. S. (2012). The Information Content of Trade Credit. Journal of Banking and Finance 36:1402–1413.Allayannis, G., Gregory, W. B., & Leora, F. K. (2003). Capital Structure and Financial Risk: Evidence from Foreign Debt use in East Asia. The Journal of Finance 58:2667–2709.Almilia, L., & Kristijadi, E. (2003). Analisis Rasio Keuangan untuk Memprediksi Kondisi Financial Distress Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Jakarta. Jurnal Akuntansi dan Auditing Indonesia (JAAI), Vol 7, No2: 1-27.Altman, E. I. (1968). Financal Ratio, Discriminant Anlysis and the Prediction of Comparate Bankruptcy. The Journal of Finance, Vol.XXIII No.4: 589-609.Altman, E. I., Alessandro, D., & Falini, A. (n.d.). Z-SCORE MODELS’ APPLICATION TO ITALIAN COMPANIES SUBJECT TO EXTRAORDINARY ADMINISTRATION.Altman, Edward, I., John, H., & Peck, M. (1997). Emerging Market Corporate Bonds: A Scoring System. New York: Salomon Brothers. In Future of Emerging Market Flows. Edited by Richard M. Levich and J. P. Mei.Assaji, J., & Zaky, M. (2017). Rasio Keuangan dan Prediksi Financial Distress. Jurnal Penelitian Ekonomi dan Bisnis.Babatunde, A. A., Akeju, J. B., & Malomo, E. (2017). The Effectiveness of Altman's Z-score in Predicting Bankruptcy of Quoted Manufacturing Companies in Nigeria. European Journal of Business, Economics and Accountancy, Vol. 5. No. 5.Batubara, E. J. (2014). Analisis Pengaruh Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Profit Margin (NPM), dan Return on assets (ROA) terhadap harga saham. Universitas Islam Negeri Syarif Hidayahtullah Jakarta.Beaver, W. H., Maria, C., & Maureen, F. M. (2011). Financial Statement Analysis and the Prediction of Financial Distress. Foundations and Trends in Accounting, 5(2), 99–173.Brahmana, R. (2007). Identifying Financial Distress Condition in Indonesia Manufacture Industry. Journal of accounting, H. 5-51.Chen, H., Marcin, K., & Hernan, O.-M. (2011). Do Nonfinancial Stakeholders Affect the Pricing of Risky Debt? Evidence from Unionized Workers. Rev. Finance 16:347–383.Cristananda, C., Khairunnisa, & Annisa, N. (2017). Analysis of Current Ratio and Net Profit Margin for Predicting Financial Distress Condition of the Company. e-proceedings of Management, vol. 4(1).Curry, K., & Erliana, B. (2018). FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR PROPERTI GO PUBLIC DI INDONESIA. Fakultas Ekonomi dan Bisnis Universitas Trisakti.Darsono, & Ashari. (2005). Pedoman Praktis Memahami Laporan Keuangan. Yogyakarta: CV. Andi Offset.Databoks. (2018). Retrieved from Inilah Pertumbuhan Ekonomi Indonesia Sejak 1961: https://databoks.katadata.co.id/datapublish/2018/01/31/inilah-pertumbuhan-ekonomi-indonesia-sejak-1961Egbunike, C. F., Jerry, O. O., & Okenwa, O. (2019). The Effect of Financial Distress on Corporate Profitability: A Panel Estimated Generalized Least Squares (EGLS) Approach . Journal of Global Accounting, vol.6 No. 1.Foster, G. (1986). Financial Statement Analysis. New Jersey: Prentice Hall, Englewood Cliffs.Gamayuni, R. R. (2011). Analisis Ketepatan Model Altman sebagai Alat untuk Memprediksi Kebangkrutan. Jurnal Akuntansi dan Keuangan, vol. 16 No.2.Ghozali, I. (2009). Aplikasi Analisis Multivariate dengan Program SPSS. Semarang, UNDIP.Ghozali, I. (2016). Aplikasi Analisis Multivariete Dengan Program IBM SPSS 23 (Edisi 8). Semarang: Badan Penerbit Universitas Diponegoro.Ghozi, S., & Hadi, H. (2018). Analisis Regresi Data Panel Profitabilitas Bank Pembangunan Daerah (BPD) di Indonesia. Jurnal Matematika, Vol. 8, No 1,1-12.Goudie, A. W. (1987). Forecasting Corporate Failure: The Use of Discriminant Analysis within a Disaggregated Model of the Corporate Sector. Journal of the Royal Statistical Society, Series A (General), 69-81.Gujarati, D. (2012). Dasar-dasar Ekonometrika Terjemahan Mangunsong, R.C., Salemba Empat, buku 2, Edisi 5,. Jakarta.Gujarati, N., & Porter, D. C. (2009). Basic Econometric 5th Edition. New York: Mc-Graw-Hill.Harlen, Y. S., Topowijono, & Devi, F. A. (2019). ANALISIS PENGGUNAAN MODEL ALTMAN (Z-SCORE) UNTUK MEMPREDIKSI POTENSI KEBANGKRUTAN. Jurnal Administrasi Bisnis, Vol. 66 No. .Harmono. (2011). Manajemen Keuangan Berbasis Balanced Scorecard Pendekatan Teori, Kasus, dan Riset Bisnis. Jakarta: PT. Bumi Aksara.Hery. (2016). Analisis Laporan Keuangan. Jakarta: Grasindo.Hidayat, A. (2014, november 2). Statistikian. Retrieved from Penjelasan Metode Analisis Regresi Data Panel: https://www.statistikian.com/2014/11/regresi-data-panel.htmlHussain, F., Iqtidar, A., Ullah, S., & Madad, A. (2014). Can Altman Z-score Model Predict Business Failures in Pakistan? Evidence from Textile Companies of Pakistan. Journal of Economics and Sustainable Development, 5(13), 110-115.IDX. (2017). Retrieved from Indonesia Stock Exchange, Aktivitas Pencatatan: https://www.idx.co.id/perusahaan-tercatat/aktivitas-pencatatan/Iqbal, A. M. (2015). Pemikiran Pendidikan Islam. Pustaka Pelajar.Junaidi. (2012). Download table Durbin Watson, tabel F, tabel t. Retrieved from wordpress: https://junaidichaniago.wordpress.com/2010/04/21/download-tabel-t-untuk-d-f-1-200/Kasmir. (2014). Analisis Laporan Keuangan . Jakarta: Rajawali Pers.Khoriyah, S. (2019). Analisis Financial Distress, Perbandingan dan Tingkat Akurasi Menggunakan Model Altman Z-score, Grover, Springate dan Zmijewski untuk memprediksi kebangkrutan pada perusahaan. Surakarta: Institusi Agama Islam Surakarta.Kieschnick, R., Laplante, M., & Moussawi, R. (2013). Working capital management and shareholders’ wealth. Rev. Finance 17:1827–1852.Liang, F. S., & Pathak, S. (2016). Financial Health & Corporate Performance a Comparison of Manufacturing Companies in China & India. Journal of Asian Development, 2(1), 18-29.Madhushani, I. K., & Kawshala, B. A. (2018). The Impact of Financial Distress on Financial Performance: Special Reference to Listed Non-Banking Financial Institutions in Sri Lanka. International Journal of Scientific and Research Publications, 8(2), 393-405.Malhotra, K., Sathappa, M., Landin, J. S., Johnson A, E., & Alder, N. N. (2013). Structural changes in the mitochondrial Tim23 channel are coupled to the proton-motive force. 20(8):965-72.Mayang, & Murni. (2018). Analisis Faktor-faktor yang Mempengaruhi Tingkat Financial Distress pada Perusahaan Manufaktur yang Terdaftar di BEI tahun 2010-2014. Jurnal Akuntansi dan Bisnis, vol. 4(1).Muhtar, M., & Andi, A. (2017). Pengaruh Kinerja Keuangan Terhadap Terjadinya Kondisi Financial Distress pada Perusahaan Telekomunikasi di Indonesia. Jurnal Bisnis Manajemen dan Informatika, Volume 13 No. 3.Nirmalasari, L. (2018). Financial Distress analysis of Property, real estate and building construction company registered in Indonesia stock Exchange. Yogyakarta: Program Studi Manajemen Fakultas Ekonomi Universitas Negeri Yogyakarta.Platt, H. D., & Platt, M. B. (2002). 2002 predicting Financial Distress. Journal of Financial Service Proffesional.Platt, H. D., & Platt, M. B. (2002). Predicting Corporate Financial Distress: Reflections on Choice-Based Sample Bias. Journal of Economics and Finance, Volume 26 Number 2.Pranowo, K., Noer, A. A., Adler, H. M., & Nunung, N. (2010). Determinant of Corporate Financial Distress in an Emerging Market Economy.’ Empirical Evidence from the Indonesian Stock Exchange 2004-2008.Prasetyo, R. Y., Darminto, & Nuzula, N. F. (2016). Pengaruh Profitabilitas Terhadap Pertumbuhan Perusahaan. jurnal administrasi bisnis, vol. 30 no. 1.Prihadi, T. (2009). Investigasi Laporan Keuangan & Analisis Rasio Keuangan. PPM, Jakarta.Rafles, W. T., Dwiatmanto, & M.G., W. E. (2015). Analisis Prediksi Kebangkrutan Perusahaan Dengan Menggunakan Metode Altman (Z-score). Jurnal Administrasi Bisnis, vol. 2 no. 1.Ramadhani, S. A., & Lukviarman, N. (2009). Perbandingan Analisis Prediksi Kebangkrutan Menggunakan Model Altman Pertama, Altman Revisi, dan Altman Modifikasi dengan Ukuran dan Umur Perusahaan Sebagai Variabel Penjelas (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia. Jurnal Siasat Bisnis.Rezeki, D. S., Adel, J. F., & Tumpat, M. (n.d.). Analisis Rasio Keuangan Dalam Memprediksi Kondisi Financial Distress Pada Perusahaan Sub Sektor Aneka Industri Yang Terdaftar Di BEI Periode 2013 – 2016. Universitas Maritim Raja Ali Haji.Ripais, M. (2014). Pengaruh Rasio Likuiditas, Rasio Leverage, Rasio Profitabilitas Terhadap Kondisi Financial Distress Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia. Jurnal Fakultas Ekonomi Universitas Maritim Raja Ali Haji.Rizal, J., & Syahrul, A. (2015). Perbandingan Uji Stationer Data Time Series antara Metode : Control Chart, Correlogram, Akar Unit Dickey Fuller, dan Derajat Integrasi. Jurnal Gradien, 11(1), 1040-1046.Rudianto. (2013). Akuntansi Manajemen Informasi Untuk Pengambilan Keputusan Strategis. Jakarta: Erlangga.Sanjaya, S., & Rizky, M. F. (2018). Analisis profitabilitas dalam Menilai kinerja keuangan pada PT. Taspen (persero) Medan. Volume 2. No. 2.Setiawan, H., & Dheasey, A. (2018). Financial Ratio Analysis for Predicting Financial Distress Conditions (Study on Telecommunication Companies Listed In Indonesia Stock Exchange Period 2010-2016).Singhal, R., & Yun, Z. (2013). Bankruptcy risk, costs and corporate diversification. Journal of Banking & Finance 37:1475–1489.Sri, P. M. (2016). The Role of External and Internal Factors in the Accuracy of Predicting Financial Distress . European Journal of Business and Management, Vol.8, No.13, 2016 .Sugiyono. (2011). Metode Penelitian Kuantitatif, Kualitatif dan R&D . Bandung: Afabeta.Syamsuddin, L. (2011). Manajemen Keuangan Perusahaan (Konsep Aplikasi dalam: Perencanaan, Pengawasan, dan Pengambilan Keputusan). Jakarta: PT Raja Grafindo Persada.Ufo, A. (2015). Impact of Financial Distress on the profitability of selected Manufacturing firm of Ethiopia. Journal of Poverty, Investment and Development, Vol.16.Uğurlu, M., & Aksoy, H. (2006). Prediction of Corporate Financial Distress in an Emerging Market: The Case of Turkey. Journal of Cross Cultural Management, Vol. 13, h. 277-295.Umar, H. (2008). Metode Penelitian untuk Skripsi dan Tesis Bisnis. Jakarta: PT. Raja Grafindo Persada.Unegbu, A., & Adefila, J. (2013). Efficacy assessments of Z-Score and operating cash flow insolvency predictive models. Open Journal of Accounting, 3, 53-78. DOI: 10.4236/ojacct.2013.23009.Widarjono, A. (2007). Ekonometrika Teori dan Aplikasi . Yogyakarta: Ekonesia.Widarjono, A. (2009). Ekonometrika Pengantar dan Aplikasinya, Edisi Ketiga. Yogyakarta: Ekonesia.Wruck, K. (1990). Financial Distress, Reorganization, and Organizational Efficiency. Journal of Financial Economics, Vol. 27, h. 419-444.Yadiati, W. (2017). The influence of profitability on financial distress: A research on agricultural companies listed in Indonesia Stock Exchange.